In Vitro Antimicrobial Activity of Essential Oil Derived from Callistemon viminalis Aerial Part - Yasir Asaad, Anes (AL-Kindy College Medical Journal, 2023)
Background: Essential oils extracted from plants have been widely used in antimicrobial activity, particularly the Callistemon viminalis, with a high number of essential oils extracted. Objectives: To identify the chemical composition of essential oil derived from Callistemon viminalis and evaluates its antimicrobial activity against selected bacterial and fungal strains. Subjects and methods: During the study, the antimicrobial activity of different selected essential oils on some bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis, Staphylococcus aureus, and Streptococcus pneumonia) and fungus (Candida albicans) was evaluated. The MicroScan WalkAway automated device was used to confirm the identification of the bacteria microorganisms and the germ tube and microscopy detection confirmed the fungus identity of specific morphological features after growth on corn meal agar, used in this study. Results: the GC-MS analysis reveal that the chemical composition of the essential oil was contained Eucalyptol (41.17%) area, Viridiflorol (8.43%) area, Alpha-Pinene (4.53%) area, Alpha-Terpineol (4.53%) area and others. The essential oil shows activity against Staphylococcus aureus with inhibition zone diameter of 10 mm, and for Streptococcus pneumoniae, with ihibition zone of 22 mm. Conclusion: The highest antimicrobial activity was against S. aureus and S. pneumonia of Gram-positive bacteria. The study result show that resistance from Gram-negative bacteria and resistance from fungus C. albicans to the oil. These varying results of bacterial suseptabilty may be based on the construction of the bacterial cell wall between Gram-positive and Gram-negative bacteria. The essential oil components detected with higher percent area in GC-MS from C. viminalis are Eucalyptol, alpha-Pinene, Viridiflorol, beta-Eudesmol, and alpha-Tocopherol.